2017
DOI: 10.1097/md.0000000000007543
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of risk-stratification delirium prediction model for critically ill patients

Abstract: The objective is to develop a model based on risk stratification to predict delirium among adult critically ill patients and whether early intervention could be provided for high-risk patients, which could reduce the incidence of delirium.We designed a prospective, observational, single-center study. We examined 11 factors, including age, APACHE-II score, coma, emergency operation, mechanical ventilation (MV), multiple trauma, metabolic acidosis, history of hypertension, delirium and dementia, and application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 20 publications
2
50
0
7
Order By: Relevance
“…This is partly consistent with a study concluding that diabetic patients are more prone to POD 27. There are some other studies28 29 that have shown associations of ICU-POD with diabetes, acid–base imbalance, coma and hypertension. Nevertheless, to our knowledge, this is the first analysis to report on associations among all of those five risk elements together, including the POSSUM score for the first time ever, in the development of ICU-POD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is partly consistent with a study concluding that diabetic patients are more prone to POD 27. There are some other studies28 29 that have shown associations of ICU-POD with diabetes, acid–base imbalance, coma and hypertension. Nevertheless, to our knowledge, this is the first analysis to report on associations among all of those five risk elements together, including the POSSUM score for the first time ever, in the development of ICU-POD.…”
Section: Discussionsupporting
confidence: 87%
“…The model contained nine candidate predictors: Physiological and Operative Severity Score for the enumeration of Mortality and morbidity (POSSUM) score, sex, history of coma (history of transitional conscious disturbance before admission, discovered when doctors were collecting the patient’s medical history), history of hypertension (systolic blood pressure ≥140 mm Hg, with or without diastolic pressure ≥90 mm Hg; or simple hypertension with systolic blood pressure ≥140 mm Hg only diagnosed previously before admission by clinicians and had recorded in the medical record), history of diabetes (diagnosed before admission by clinicians and recorded in the medical record), mechanical ventilation, history of alcohol dependence (based on International Statistical Classification of Diseases and Related Health problems (10th Revision) (ICD-10)22 and diagnosed by clinicians), acid–base imbalance (including metabolic acidosis, metabolic alkalosis, respiratory acidosis and respiratory alkalosis, identified by the first blood gas analysis) and length of operation. For each candidate predictor, at least 5–10 patients with delirium were required based on the sample size formula for modeling23; as the minimum incidence of ICU-POD is 27.6%,3 we used this value. With an anticipated delirium incidence of 27.6% and an expected attrition of 10%–20%, we aimed to enrol at least 1960 patients (9×5 × (1+0.2) / 0.276).…”
Section: Methodsmentioning
confidence: 99%
“…As reported by multiple studies, the incidence rate of delirium is 20% to 80% in the ICU setting. [ 1 , 3 , 8 , 11 , 19 26 ] Chen et al [ 27 ] reported an incidence rate of 25.8% of delirium in their ICU in China. Similarily, Su et al [ 28 ] found that incidence of postoperative delirium was 23% in patients after noncardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…CAM-ICU and ICDSC were the most commonly used assessment tools with great reliability and validity. [ 1 , 27 , 28 ] This survey revealed that ∼16% of participants reported the use of CAM-ICU, and another 16% reported the use of ICDSC. In contrast, 34.46% of the respondents stated that they monitored delirium with multiple assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…Three prediction models have been validated to predict the risk for ICU delirium among critically ill delirium-free adults. The PRE-DELERIC [12] and the E-PRE-DELERIC [13] have been externally validated for use with both the ICDSC and the CAM-ICU, and the Lanzhou model [14] has been internally validated for use with the CAM-ICU. Another model, the dynamic Acute Brain Dysfunction-prediction model (ABD-pm) [15], has been internally validated using the CAM-ICU to predict next day status (i.e., normal, delirium, coma, ICU discharge or ICU death) among critically ill adults including those with delirium at time of ICU admission.…”
Section: Introductionmentioning
confidence: 99%